Ответ:
a) 12 sqrt (2) - 12 sqrt (3) = 12 × (sqrt(2)-sqrt(3))
b) t + sqrt(t) = sqrt (t) × (sqrt (t) + 1)
c) 3 sqrt(a³) + 3a = 3 × (sqrt(a³) + a) = 3a × (sqrt(a) + 1)
d) 9 sqrt(7) + sqrt(28) = 9 sqrt(7) + 2 sqrt(7) = 11 × sqrt(7)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
a) 12 sqrt (2) - 12 sqrt (3) = 12 × (sqrt(2)-sqrt(3))
b) t + sqrt(t) = sqrt (t) × (sqrt (t) + 1)
c) 3 sqrt(a³) + 3a = 3 × (sqrt(a³) + a) = 3a × (sqrt(a) + 1)
d) 9 sqrt(7) + sqrt(28) = 9 sqrt(7) + 2 sqrt(7) = 11 × sqrt(7)